Ensemble of Convolutional Neural Networks for Medicine Intake Recognition in Twitter - Kai Hakala; Farrokh Mehryary; Hans Moen; Suwisa Kaewphan; Tapio Salakoski; Filip Ginter (My University, 2022)
We present the results from our participation in the 2nd Social Media Mining for Health Applications Shared Task – Task 2. The goal of this task is to develop systems capable of recognizing mentions of medication intake in Twitter. Our best performing classification system is an ensemble of neural networks with features generated by word- and character-level convolutional neural network channels and a condensed weighted bag-of-words representation. A relatively strong performance is achieved, with an F-score of 66.3 according to the official evaluation, resulting in the 5th place in the shared task with performance close to the best systems created by other participating teams.
Proceedings of the 2nd Social Media Mining for Health Research and Applications Workshop (SMM4H 2017)